Morphological Characteristics and Morphometry of The Kidneys and Testis in 6-Month-Old Rats Under Conditions of Zinc Deficiency - Baymuradov , R.R.; Teshayev , Sh.J. (American Journal of Biomedicine and Pharmacy, 2026)
This study investigated the morphological and morphometric changes in the kidneys and testes of 6-month-old rats under conditions of zinc deficiency. The results demonstrated glomerular hemodynamic disturbances, tubular epithelial atrophy, and interstitial remodeling in the kidneys, as well as thinning of the spermatogenic epithelium, a decrease in germ cell number, and reduced Leydig cell density in the testes. Evaluation using the Johnsen scoring system confirmed impairment in the final stages of spermatogenesis. The findings indicate that zinc deficiency leads to structural and functional remodeling of the renal and reproductive systems against the background of oxidative stress and trophic disturbances.